A Control Packet Minimized Routing Protocol for Ad-hoc Wireless Networks - Youn-Sik Hong (Institute of Advanced Engineering and Science, 2014)
AODV routing protocol is intended for use by mobile nodes in ad-hoc wireless networks. As the degree of node mobility becomes high, however, the number of RREQ and RREP messages during the route discovery process increase so rapidly. The unexpected increases in the number of control packets cause the destination node to decrease the packet receiving rate. Besides, the overall energy consumption for the network can be increased. Thus, we propose a novel method of adaptively controlling the occurrences of the control packets based on AIAD (additive increase additive decrease) under a consideration of the current network status. We have tested our proposed method with both the conventional AODV and the method using timestamp based on the three performance metrics; i.e., node mobility, node velocity, and node density, to compare their performances. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4179